Using nominal group technique to identify barriers and facilitators to preventing HIV using combination same-day pre-exposure prophylaxis and medications for opioid use disorder - William H. Eger; Frederick L. Altice; Jessica Lee; David Vlahov; Antoine Khati; Sydney Osborne; Jeffrey A. Wickersham; Terry Bohonnon; Lindsay Powell; Roman Shrestha (Harm Reduction Journal, 2022)
Abstract Background Preventing HIV transmission among people who inject drugs (PWID) is a key element of the US Ending the HIV Epidemic strategy and includes both pre-exposure prophylaxis (PrEP) and medications for opioid use disorder (MOUD). While both lead to decreases in HIV transmission, MOUD has other social and health benefits; meanwhile, PrEP has additional HIV prevention advantages from sexual risk and the injection of stimulants. However, these medications are often prescribed in different settings and require multiple visits before initiation. Strategies to integrate these services (i.e., co-prescription) and offer same-day prescriptions may reduce demands on patients who could benefit from them. Methods Nominal group technique, a consensus method that rapidly generates and ranks responses, was used to ascertain barriers and solutions for same-day delivery of PrEP and MOUD as an integrated approach among PWID (n = 14) and clinical (n = 9) stakeholders. The qualitative portion of the discussion generated themes for analysis, and the ranks of the proposed barriers and solutions to the program are presented. Results The top three barriers among PWID to getting a same-day prescription for both PrEP and MOUD were (1) instability of insurance (e.g., insurance lapses); (2) access to a local prescriber; and (3) client-level implementation factors, such as lack of personal motivation. Among clinical stakeholders, the three greatest challenges were (1) time constraints on providers; (2) logistics (e.g., coordination between providers and labs); and (3) availability of providers who can prescribe both medications. Potential solutions identified by both stakeholders included pharmacy delivery of the medications, coordinated care between providers and health care systems (e.g., case management), and efficiencies in clinical care (e.g., clinical checklists), among others. Conclusions Implementing and sustaining a combined PrEP and MOUD strategy will require co-training providers on both medications while creating efficiencies in systems of care and innovations that encourage and retain PWID in care. Pilot testing the co-prescribing of PrEP and MOUD with quality performance improvement is a step toward new practice models.